1990
DOI: 10.1002/cne.903020414
|View full text |Cite
|
Sign up to set email alerts
|

On the organization of astrocytic gap junctions in rat brain as suggested by LM and EM immunohistochemistry of connexin43 expression

Abstract: Gap junctions and the intercellular communication syncytium they form between glial cells are thought to play a critical role in glial maintenance of appropriate metabolic environments in neural tissues. We have previously suggested (Yamamoto et al., Brain Res. 508:313-319, '90) that the vast majority of astrocytes in rat brain express connexin43, one of several recently identified gap junction proteins. Here, we confirm ultrastructurally that astrocytes in a number of brain regions of rat are immunolabelled w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
148
0
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(156 citation statements)
references
References 95 publications
6
148
0
2
Order By: Relevance
“…Neuronal somata in the adult LC are ensheathed by one or more thin glial processes (Shimizu and Imamoto, 1970;Groves and Wilson, 1980), just as in other brain regions, where thin-section immunoEM revealed labeling for Cx43 on gap junctions between astrocyte processes but not between astrocytes and neurons (Yamamoto, et al, 1990a(Yamamoto, et al, ,1990b(Yamamoto, et al, ,1992Nagy et al, 2004). By immunofluorescence, these Cx43-positive puncta often surround neurons, giving the appearance of Cx43 puncta on neuronal somata, as observed in the present study.…”
Section: Possible Sources Of Observed Dye Coupling Of Astrocytes To Nsupporting
confidence: 83%
See 1 more Smart Citation
“…Neuronal somata in the adult LC are ensheathed by one or more thin glial processes (Shimizu and Imamoto, 1970;Groves and Wilson, 1980), just as in other brain regions, where thin-section immunoEM revealed labeling for Cx43 on gap junctions between astrocyte processes but not between astrocytes and neurons (Yamamoto, et al, 1990a(Yamamoto, et al, ,1990b(Yamamoto, et al, ,1992Nagy et al, 2004). By immunofluorescence, these Cx43-positive puncta often surround neurons, giving the appearance of Cx43 puncta on neuronal somata, as observed in the present study.…”
Section: Possible Sources Of Observed Dye Coupling Of Astrocytes To Nsupporting
confidence: 83%
“…Early on, it was proposed that neurons share gap junctions only with neurons, and that glia share intercellular gap junctions only with glia (Brightman and Reese, 1969;Mugnaini, 1986). This "restricted coupling partner" hypothesis gained support based on TEM and FRIL immunocytochemical data showing that neuronal, astrocytic and oligodendrocytic gap junctions each express different complements of connexins Nagy and Dermietzel, 2000;Rash et al, 2000Rash et al, , 2001bKamasawa et al, 2005;Fukuda et al, 2006), with Cx43, Cx30 and (in limited areas) Cx26 in astrocytes and leptomeninges (Li et al, 1997;Nagy et al, 1999Nagy et al, ,2001Rash et al, 2001b); Cx29, Cx32 and Cx47 in oligodendrocytes (Rash et al, 2001a(Rash et al, ,2001bNagy et al, 2004;Kamasawa et al, 2005); and Cx36 exclusively in neurons (Rash et al, 2001b;Fukuda et al, 2006), extending data from immunofluorescence analysis and thin-section immunocytochemistry (Yamamoto et al, 1990a(Yamamoto et al, ,1990bScherer et al, 1995;Mercier and Hatton, 2001;Altevogt et al, 2002;Kleopas et al, 2004;Rash et al, 2005).…”
Section: Connexin Composition Of Neuronal Vs Glial Gap Junctions In Lcmentioning
confidence: 99%
“…The presence of Cx 43 in radial glial fibers during the period of neuronal migration suggests that neurons establish contact and communication with the scaffolding they use as they migrate to the cortical plate. As neuronal migration tapers off, radial glial cells are transformed into fibrillary and protoplasmic astrocytes (Choi and Lapham, 1978;Schmechel and Rakic, 1979) and are added to the existing population of astrocytes known to form networks connected by gap junctions in the cortex (Bennett and Goodenough, 1978;Massa and Mugnaini, 1982;Yamamoto et al, 1990). The localization of Cx 43 in radial glia indicates that these cells possess the necessary Cxs to form gap junctions.…”
Section: Gap Junctions and Expression Of Cxs During Corticogenesismentioning
confidence: 99%
“…Anatomical and functional studies of the rodent CNS have demonstrated that astrocytes and oligodendrocytes are coupled by gap junctions (Massa and Mugnaini 1982;Ransom and Kettenmann 1990;Robinson et al 1993;Rash et al 1997), and that each cell type expresses different connexins (Dermietzel et al 1989;Yamamoto et al 1990;Scherer et al 1995;Dermietzel et al 1997;Ochalski et al 1997;Nagy et al 1999;Altevogt et al 2002;Menichella et al 2003;Odermatt et al 2003;Kleopa et al 2004). Astrocyte/astrocyte (A/ A) coupling is likely mediated by Cx43/Cx43 and Cx30/Cx30 homotypic channels, and astrocyte/oligodendrocyte (A/O) coupling is most likely mediated by Cx43/Cx47 and Cx30/ Cx32 heterotypic channels, with an uncertain contribution of Cx26/Cx32 channels (Rash et al 2001;Nagy et al 2003;Altevogt and Paul 2004;Li et al 2004).…”
mentioning
confidence: 99%